Effectiveness of N-waves for predicting morphological changes due to tsunamis - Chacon-Barrantes, Silvia (2018)
The research on morphological changes caused by tsunamis has increased considerably in the last few years, yet the processes behind this phenomenon are still not fully understood. This paper analyzes and compares numerical simulations of morphological changes caused by the leading elevation and leading depression N-waves and tsunami waves propagating over a channel with a simple bed slope. The simulations were carried out by means of a coupled flow, sediment transport and morphodynamic two-dimensional-vertical numerical model. The modeled channel bed was composed of cohesionless sediments, and range of values for the bed slope and the wave height were employed. Four tsunami waveforms were studied to test the appropriateness of N-waves in modeling the morphological changes caused by tsunamis. On the modeling performed here, runup values were quite well represented by N waves. N-waves also represented qualitatively well the morphological changes caused by tsunamis. Yet, values of flow velocities and suspended sediment concentration showed more severe deviations from the modeled results corresponding with tsunami waves, very likely due to differences on the steepness of the waves. Therefore, even when N-waves can and have been used to represent tsunami runup and inundation distance, our results suggest that they should be considered with caution when intended to predict magnitudes of tsunami flow velocities and consequently morphological changes. The use of N waves to simulate morphological changes caused by tsunamis is not yet converging and must be further investigated.